Reassessing Adaptational Lag in Eriophorum vaginatum: Short-Term Responses to Reciprocal Transplant and Passive Warming Experiments in Northern Alaska - Jennifer Lynn Chandler; James B McGraw; Michael L Moody; Jianwu Tang; Janice Voltzow; Ned Fetcher (Arctic Science)
Previous Eriophorum vaginatum studies have detected adaptational lag in response to climate change. We revisited this concept through a short-term reciprocal transplant experiment combined with warming via open-top chambers (OTCs). We asked: 1) if population growth rates of different ecotypes responded differently to reciprocal transplant, 2) if home-site advantage existed, and 3) if an interaction of ecotype, transplant garden, and OTC treatment existed. We established three transplant gardens, two north of the Brooks Range (Toolik and Sagwon) and one south (Coldfoot); OTCs were deployed in northern gardens. We censused tillers in 2016 and 2017. Lefkovitch matrices were jackknifed using Yellow Taxi Analysis to quantify each tiller’s contribution to population growth rate, which were incorporated into nested ANOVAs. Of tussocks grown in ambient temperature, mean tiller population growth from different source ecotypes did not respond differently to transplant. Home site advantage was not observed among tillers not exposed to warming via OTC, which may indicate adaptational lag is occurring. Mean population growth rate of OTC-exposed tillers was higher at Toolik than Sagwon. This study’s short duration likely limited our ability to detect differences in tiller population growth as a function of garden or ecotype, emphasizing the need for long-term monitoring.